Relationships among social support, healthy lifestyle beliefs, physical literacy, and enjoyment of physical activity: a moderated mediation model - Mehmet Akif Yücekaya; Sinan Uğraş; Ahmet Enes Sagin; Arif Çetin; Teodora-Mihaela Iconomescu; Laurențiu-Gabriel Talaghir (Frontiers in Public Health)
ObjectiveThis study aims to examine the relationships between social support, physical literacy, and healthy lifestyle beliefs in adolescents and to investigate the moderating effect of enjoyment of physical activities on these relationships.MethodThe study was conducted with the participation of 1,349 adolescents. The ages of the participants ranged between 10 and 14 years, and 49.6% were male (n = 669) and 50.4% were female (n = 680). Data were collected using the Healthy Lifestyle Belief Scale for Adolescents to measure adolescents' healthy lifestyle beliefs, the Perceived Physical Literacy Scale for Adolescents (PPLSA) to determine their physical literacy levels, the Social Support Scale in Physical Activities to assess the perception of social support, and the Enjoyment of Physical Activity Scale to measure the level of enjoyment of physical activities. The study tested the moderated mediation model for its association among the variables.ResultsThe model developed in this study found social support in PA predicted health lifestyle beliefs, positively, and significantly. Social support and perceptions of a healthy lifestyle are moderated by physical literacy, research shows. A further analysis also found that the relationship between physical literacy and social support is moderated by enjoyment of physical activities. However, the association between social support and healthy lifestyle beliefs and between physical literacy and healthy lifestyle beliefs were not appreciably influenced by enjoyment in physical activity. The findings indicated that social support has a positive and significant effect on physical literacy and attitudes toward healthy lifestyle. Physical literacy was identified as a central contributor to improving adolescents' health habits by mediating the relationship between social support and conceptions of healthy living. However, the enjoyment of fitness did not matter in some situations, the study found. These results further illustrate the importance of promoting social support and physical literacy instruction to promote a wellness lifestyle adoption by adolescents. The possible long-term effects of feeling good about exercising in various settings, and for health-related habits, should receive more scrutiny.